COVID-19 vaccination passport: prospects, scientific feasibility, and ethical concerns - Khan Sharun; Ruchi Tiwari; Kuldeep Dhama; Ali A. Rabaan; Saad Alhumaid (Human Vaccines & Immunotherapeutics, 2021)
A vaccination passport (also known as “vaccination certificate,” “immunization passport,” or “digital health pass”) is a document that provides proof of vaccination and certifies that the holder is protected from illness. It is a more reliable and practical substitute for immunity passports since COVID-19 vaccination is considered a better correlate of protection. Vaccination passport can be considered as a tool offering the holder the privilege of traveling freely within countries without any restrictions. The majority of the countries that are dependent on travel and tourism have exhibited a positive inclination toward implementing COVID-19 vaccination passports, while others have a mixed opinion. The successful implementation of vaccination passports will be a complex task for the policymakers as it requires addressing several ethical, legal, and data security concerns outlined in this article. However, vaccination passports can offer economic and health benefits that will allow the gradual recovery of the economy.